Increasing protein content and digestibility in sorghum grain with a synthetic biology approach. (January 2019) - Liu, Guoquan; Gilding, Edward K.; Kerr, Edward D.; Schulz, Benjamin L.; Tabet, Basam; Hamaker, Bruce R.; Godwin, Ian D.
Abstract: Despite great genetic diversity, sorghum grain consistently suffers from poor protein digestibility. The physicochemical packaging of protein bodies which consist of protease-resistant β - and γ -kafirin is considered a major obstacle. A synthetic β -kafirin gene, which shares the endosperm-specific promoter and signal peptide with the native β -kafirin gene ( Sobic.009G001600.1 ), was transformed into sorghum inbred line Tx430. The gene was modified with ten additional proteolytic sites. These sites were designed to be amenable to cleavage by pepsin and/or chymotrypsin proteinases. Five independent transgenic lines were regenerated by microprojectile transformation. Notably, considerably more protein was observed in the peripheral endosperm of transgenic lines under scanning electron microscopy. Microscopy revealed invaginated or irregularly shaped protein bodies in the endosperm of transgenic lines. Grains of transgenic lines contained 11–37% more protein, which was 11–21% more pepsin digestible and 7–25% more chymotrypsin digestible than Tx430. Additionally, the abundant synthetic β -kafirin protein (5.6% of total protein) was detected by mass spectrometry data analysis in the transgenic line 9-1. Field-grown homozygous transgenics retained higher protein content, larger seed size and no reduction in grain number per plant. The results illustrated that plant synthetic biology could play an important role in improving sorghum nutritional value. Highlights: Endosperm-specific expression of a synthetic beta-kafirin gene increased grain protein by up to 37%. The synthetic beta-kafirin gene enhanced protein digestibility by up to 21% in sorghum grain. Abundant synthetic beta-kafirin protein was detected by mass spectrometry data analysis. Transgenic lines had thicker peripheral endosperm filled with altered protein bodies.